2003
DOI: 10.1046/j.1525-1497.2003.20512.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction in women’s clinics versus traditional primary care clinics in the veterans administration

Abstract: OBJECTIVE:To compare patient satisfaction in women's clinics (WCs) versus traditional primary care clinics (TCs).DESIGN: Anonymous, cross-sectional mailed survey.SETTING: Eight Department of Veterans Affairs (VA) medical centers in 3 states.PATIENTS: A random sample of women stratified by site and enrollment in WC versus TC (total response rate = 61%). MEASURES:Overall satisfaction and gender-specific satisfaction as measured by the Primary Care Satisfaction Survey for Women (PCSSW). ANALYSIS:We dichotomized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 20 publications
5
39
0
Order By: Relevance
“…These results suggest that women's primary care clinics, which are available at many VHA facilities, are a strategic setting to enhance implementation of women's mental health services through integration of primary care and mental health care (36). These data are also consistent with prior research that has found that designated women's primary care services are associated with greater satisfaction among female veterans (37,38), as well as higher ratings of patient centeredness, such as patient-provider communication, provider's interest in mental health, provider's expertise with women, and shared decision making (39). Future research should examine whether meeting these preferences is similarly associated with greater engagement and satisfaction with mental health services.…”
Section: Discussionsupporting
confidence: 82%
“…These results suggest that women's primary care clinics, which are available at many VHA facilities, are a strategic setting to enhance implementation of women's mental health services through integration of primary care and mental health care (36). These data are also consistent with prior research that has found that designated women's primary care services are associated with greater satisfaction among female veterans (37,38), as well as higher ratings of patient centeredness, such as patient-provider communication, provider's interest in mental health, provider's expertise with women, and shared decision making (39). Future research should examine whether meeting these preferences is similarly associated with greater engagement and satisfaction with mental health services.…”
Section: Discussionsupporting
confidence: 82%
“…Results may also not generalize to heterosexual women (especially the lesbian-specific findings), although some of the priorities of women in our sample mirror those of general populations of women participating in parallel studies. 22,39 Results also may not be generalizable to elderly lesbians; the oldest participant in our study was 63 years old. Another limitation is that participants self-identified as lesbian; their responses may not represent the views of lesbians who would be uncomfortable disclosing their sexual orientation in any setting, even a confidential focus group.…”
Section: Discussionmentioning
confidence: 85%
“…27 Further research should explore patient perception of and navigation among the many VA clinical sites that serve as entry points for OEF/OIF women veteran (e.g., post-deployment clinics, women's clinics, primary care clinics, and mental health clinics). 28 A limitation of this study is that we did not assess the seriousness of the condition for which healthcare was delayed or not obtained, the length or number of delays over 12 months, or the health consequences. Nonetheless, our measure allows comparison with non-veteran populations, and is a useful starting point for a follow-up study to better characterize unmet need and to address potential solutions.…”
Section: Discussionmentioning
confidence: 99%